An Integrated Analysis of Transcriptomic and Metabolomic Effects Reveals Insights into Stress Responses in Largemouth Bass (Micropterus salmoides) Under MS-222 (Tricaine Methanesulfonate) Exposure - Ping Gao; Rimeng Chen; Deyun Ma; Shanshan Lin; Haodong Yu; Xuezhen Zhang (Metabolites)
Background/Objectives: MS-222 is a commonly used anesthetic for fish. Research on the anesthetic mechanism of MS-222 is scarce, especially in largemouth bass. Therefore, this study investigated the tissue-specific transcriptomic and metabolomic effects of MS-222 anesthesia on largemouth bass (Micropterus salmoides). Methods: Experimental groups exposed to 40 mg/L MS-222 for 12 h were compared with untreated controls, and then transcriptomic and metabolomic analyses were performed on gill and liver samples. Results: Gill tissues exhibited 3252 differentially expressed genes (DEGs; 2309 upregulated and 943 downregulated) enriched in cardiac muscle contraction, cytoskeletal regulation, glycolysis, and toll-like receptor pathways for anesthetic adaptation. In contrast, liver tissues showed fewer DEGs (1140; 654 upregulated and 486 downregulated) primarily linked to metabolic network reorganization such as endoplasmic reticulum protein processing, PPAR signaling, and ribosome biogenesis. Metabolomic profiling demonstrated inverse patterns, with 173 differential metabolites in gills versus 297 in liver samples. Methyl nicotinate and N-acetyl-L-phenylalanine were the most significantly upregulated in the gill and liver samples. Metabolic pathway enrichment analysis revealed that MS-222-induced differential metabolites in the gill and liver of largemouth bass were predominantly associated with pathways involved in amino acid, fatty acid, phenylalanine, and nucleotide metabolism. Conclusions: These findings reveal that MS-222 anesthesia triggers organ-specific physiological adaptations through the differential regulation of metabolic and immune pathways, which provide multi-omics insights into the mechanistic basis of anesthetic responses in fish, highlighting distinct tissue strategies for managing chemical stress.